Sobre el venezolanismo arrochelado - Obediente Sosa, Enrique (El Colegio de México, 2019)
The present note reflects on the term arrochelado, contributing informationor details about its origin and, in particular, about the dating of its differentmeanings. The different sense that the term has acquired over time will be presented as well as the diatopic extension of the word. In order to achieve this, we will begin by resuming what has already been masterfully expounded by the great philologist Ángel Rosenblat, and then expand on this offering new documentary sources and digital corpora which have subsequently enriched our knowledge of the Spanish lexicon in its different varieties.